1986
DOI: 10.1111/j.1476-5381.1986.tb10235.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐dependent contractile response of arterial smooth muscle to a jellyfish toxin (pCrTX: Carybdea rastonii)

Abstract: 1 The purpose of the present experiments was to investigate the pharmacological mechanisms of the vasoconstriction caused by the toxin (pCrTX) which had been partially purified from the tentacles of the jellyfish Carybdea rastonii ('Andonkurage').2 pCrTX (0.1 to 10 ptg ml'-l) produced a tonic contraction of rabbit aortic strips, which was nearly abolished in Ca2+-free medium and was significantly reduced by verapamil or diltiazem. 3 pCrTX stimulated 45Ca2+-influx and this effect was markedly attenuated by vera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…pCrTX has also been reported to cause contractions in rabbit aorta by releasing norepinephrine from adrenergic nerve terminals and by increasing the transmembrane Ca 2ϩ influx (21). Furthermore, pCrTX relaxes norepinephrine-induced contractions in rat aorta, and this may be due to the release of an endothelium-derived relaxing factor (22).…”
Section: Toxicity Of Crtxsmentioning
confidence: 97%
“…pCrTX has also been reported to cause contractions in rabbit aorta by releasing norepinephrine from adrenergic nerve terminals and by increasing the transmembrane Ca 2ϩ influx (21). Furthermore, pCrTX relaxes norepinephrine-induced contractions in rat aorta, and this may be due to the release of an endothelium-derived relaxing factor (22).…”
Section: Toxicity Of Crtxsmentioning
confidence: 97%
“…It is well-documented that these substances have physiological and toxicological effects such as lethal toxicity on mammals, hemolytic activity, dermonecrotic activity, and cardiotoxic effects (2). Beside these toxic effects, allergic mechanisms may play a role in the general reactions caused by jellyfish stings.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous report showed that the pCrTX-induced contraction was partially in hibited by verapamil (2). In the present experiment, we re-examined this in the tissue from which adventitia and endothelium had been removed.…”
Section: Discussionmentioning
confidence: 99%
“…A toxic component extracted from the tentacles of the jellyfish (pCrTX) has been shown to induce platelet aggregation (1 ). pCrTX has also been reported to cause a contraction in rabbit aorta by releasing noradrenaline from adrenergic nerve terminals and by increasing transmembrane Ca 21 influx (2) and to inhibit the contraction in rat aorta by releasing a relaxant substance from the endothelium (3).…”
Section: Abstract-effectsmentioning
confidence: 99%